Muhammad Syahrur's Thoughts on the Term Nisa' in the Al-Qur'an Surah Ali Imran: 14 (Hermeunetical Studies) - Syamsul Amri; Arifinsyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Muhammad Syahrur, a renowned Islamic thinker in the contemporary era, has made significant contributions in this field. According to Syahrur, there is no need to stick to traditional interpretations in understanding the verses of the Koran. For example, in his analysis of QS. Ali-Imran: 14, he suggests that the word